Prevalence, Pattern, and Socioeconomic Consequences of Menstrual Disorders Among Women of Reproductive Age in Ibadan, Nigeria (Nigerian Journal of Pharmaceutical Research, 2026)
Background: Menstrual disorders, including dysmenorrhoea, amenorrhoea, abnormal vaginal bleeding, premenstrual syndrome (PMS), and menorrhagia, are major causes of gynaecological consultations and negatively affect women’s health and productivity. Despite their significance, evidence from low- and middle-income countries remains limited. Objectives: This study assessed the prevalence, pattern, and socioeconomic consequences of menstrual disorders among women of reproductive age in Ibadan, Nigeria.Methods: A cross-sectional survey of 560 women attending three hospitals in Ibadan was conducted using a structured questionnaire. Descriptive statistics was used to summarise the findings. Associations were tested with Pearson’s chi-square and, logistic regression identified sociodemographic predictors and impacts of menstrual disorders. Statistical significance was set at ρ≤0.05.Results: A total of 89.0% of respondents reported at least one menstrual disorder. PMS was most prevalent (69.5%), followed by dysmenorrhoea (59.5%) and menorrhagia (13.6%). Although 84.5% reported regular cycles and 69.8% had 3–5 days of flow, pain from menstrual disorders disrupted daily activities in 61.4% and caused work absenteeism in 44.6%. Only 8.4% had ever been hospitalised, while 65.2% expressed reluctance towards menstruation. Being unmarried was significantly associated with lower odds of dysmenorrhoea compared to married women [AOR=0.68, 95% CI: 0.48–0.99]. Dysmenorrhoea was associated with lower odds of concentration disruption [AOR=0.52, 95% CI: 0.34–0.81] and approximately doubled the odds of work disability [AOR=2.04, 95% CI: 1.32–3.23]. Menorrhagia was significantly associated with increased odds of social isolation [AOR=2.50, 95% CI: 1.39–4.55].Conclusion: Menstrual disorders are highly prevalent among women in Ibadan and substantially affect daily functioning, work productivity, and perceptions of menstruation. Targeted interventions are required to improve menstrual health and mitigate socioeconomic consequences.